The Use of PTP Online about Teacher Written Feedback to Enhances Students' Understanding in Writing Skills - Sari, Vivin Purnama; Swara, Marrieta Moddies (Foremost Journal, 2022)
The aim of this research was to know whether there is significant effect of The Use of Peer-To-Peer (PTP) Online about Teacher Written Feedback to Enhances Students' Understanding in Writing Skills at Second Semester Grade of English Language Education Faculty of Teacher Training and Education of Universitas Islam Syekh-Yusuf Tangerang. This research is quantitative method, 26 students as the sample which taken nonrandom by using quasi experimental research-time series design. Students' test and questionnaires were used by the researcher to collect the data. Based on hypotheses testing by using Wilcoxon Signed Ranks test, it is shown that sig (0.000) is smaller than 0.05. This knows that the hypotheses (Ho) was rejected and the hypotheses (Ha) was accepted. It means that, there was significant difference used Peer-to-Peer Online about Teacher Written Feedback to Enhances Students' Understanding in writing skill at the second semester grade of English Language Education Faculty of Teacher Training and Education of Universitas Islam Syekh-Yusuf Tangerang, because the condition of students' were same proficiency, had concentration, focused, and students in experimental class had many opinions during the learning. The acquired results of this research indicated that using Peer-to-Peer Online about Teacher Written Feedback can improve students' writing skill.